A-Z Lezingen : 2009-2010. - Bijnens, Helena; Huygens, Ils; Peeters, Iris; Stuyck, Willy; Tassinari, Virginia; Vandebosch, Johan; Van Loon, Heleen; Willems, Bert (Hasselt : Bert Willems, 2010)
Meskens, Ann ; Fairs, Marcus ; Bijl, Guillaume ; Bowen, Simon ; NJIRIC + ; Happel Cornelisse ; Dierendonck-Blancke ; Bowen, Simon ; Van Kouswijk, Manon ; Lefteri, Chris ; Ferrara, Luigi ; Restelli, Beba ; Munari, Bruno ; Schuiten, Luc ; Lommée, Thomas ; PUUR
boek